Breathable and Skin‐Conformal Electronics with Hybrid Integration of Microfabricated Multifunctional Sensors and Kirigami‐Structured Nanofibrous Substrates. (26th May 2022) - Li, Hegeng; Wang, Zuochen; Sun, Mingze; Zhu, Hengjia; Liu, Hongzhen; Tang, Chuyang Y.; Xu, Lizhi
Abstract: Skin‐integrated soft electronics have attracted extensive research attention due to their potential utility for fitness monitoring, disease management, human–machine interfaces, and other applications. Although many materials and device components are explored for the construction of skin‐integrated systems, achieving multifunctional sensor platform combined with good breathability and conformability on the skin remains difficult. This challenge is partly due to the processing incompatibility between planar‐fabricated microelectronics and biocompatible porous substrates. Here, a fabrication strategy that can overcome this limitation, leading to large‐area multifunctional skin electronics with breathability and conformability required for wearable applications, is reported. In this scheme, a hybrid integration of high‐performance microfabricated sensors and nanofibrous soft substrates is made possible with stamp‐based transferring techniques combined with electrospinning. The resulting membrane devices exhibit tissue‐like mechanical properties with high permeability for vapor transport. In addition, kirigami structures can be introduced into these membranes, providing high stretchability and 3D conformability for large‐area integration on the skin. The multifunctional sensors array allow for spatiotemporal measurement of bioelectrical signals, temperature, skin hydration, and potentially many other physiological parameters. The robust performance and manufacturing scalability provided by these multifunctional skin electronics may create further opportunities for the development of advanced wearable systems. Abstract : Large‐area multifunctional skin electronics with high breathability and conformability are important for wearable applications. To engineer the essential device components, a hybrid integration of high‐performance microfabricated sensors and permeable nanofibrous substrates is made possible with stamp‐based transferring techniques combined with electrospinning. Kirigami structures introduced into these membranes provide further stretchability and 3D conformability for large‐area integration on the skin.